2008
DOI: 10.1007/s00404-008-0748-7
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the outcome of bloodless emergency laparotomies on Jehovah’s Witness women presenting in the extremis with ruptured uterus

Abstract: Patients who are in haemorrhagic shock from ruptured uterus and refuse blood transfusion can still be salvaged in a low resource setting. The study adds evidence that major operative procedures can be carried out on Jehovah's Witness patients without blood transfusions or blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Gynecological operations, including ruptured uterus operation, open heart surgery, and organ transplantation without transfusion, have been reported to be of comparable risk to conventional transfusion administered to patients in identical situations [11][12][13][14]. As in the case of noncancer surgery, almost all of the cancer surgeries evaluated in this study were conducted without any of the complications associated with bloodless treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gynecological operations, including ruptured uterus operation, open heart surgery, and organ transplantation without transfusion, have been reported to be of comparable risk to conventional transfusion administered to patients in identical situations [11][12][13][14]. As in the case of noncancer surgery, almost all of the cancer surgeries evaluated in this study were conducted without any of the complications associated with bloodless treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Others followed and treatment of complex procedures including cardiac, orthopaedic and cancer surgery was progressively able to be performed as experience increased. Publication of results not only showed that patients were surviving complex procedures without the use of transfusion, but that their outcomes were as good as, if not better than, similar patients who received blood transfusion [89][90][91][92][93][94][95][96][97][98][99]. With news of treatment success, other Witness patients as well as other patients who preferred to avoid allogeneic blood for any reasons, were attracted to the care of these clinicians and the foundations for the early 'bloodless programmes' was laid [80,100,101].…”
Section: A New Way Of Practicing: Patient Blood Managementmentioning
confidence: 99%
“…(2)(3)(4)(5) These data seem to support the plasticity that the human body has to compensate for blood loss and overcome difficulties in oxygen transportation and suggest that lower hemoglobin and hematocrit levels than those used in transfusion decision making are perfectly acceptable without using RBCT. (6,7) In addition, the use of alternative transfusion procedures in the pre-and intraoperative periods including red cell recovery, hemodilution with crystalloids, an increased oxygen supply, use of erythropoietin, iron and vitamin B12 supplements, has reduced the effect of blood loss and does not result in changes related to hypoxia, hypotension or arrhythmia. (6)(7)(8)(9)(10) It has also been noted that there are great intra-and inter-institutional variations in RBCT protocols when performing procedures such as coronary artery bypass, acute coronary syndrome and orthopedic surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…(6,7) In addition, the use of alternative transfusion procedures in the pre-and intraoperative periods including red cell recovery, hemodilution with crystalloids, an increased oxygen supply, use of erythropoietin, iron and vitamin B12 supplements, has reduced the effect of blood loss and does not result in changes related to hypoxia, hypotension or arrhythmia. (6)(7)(8)(9)(10) It has also been noted that there are great intra-and inter-institutional variations in RBCT protocols when performing procedures such as coronary artery bypass, acute coronary syndrome and orthopedic surgeries. (11)(12)(13)(14) Furthermore, the documentation in medical records in respect to requests for transfusions and the monitoring of side effects of RBCT is often scarce.…”
Section: Introductionmentioning
confidence: 99%